Effects of acute hCG stimulation on serum INSL3 and 25‐OH vitamin D in Klinefelter syndrome. (12th July 2020) - Santi, Daniele; Ivell, Richard; Anand‐Ivell, Ravinder; De Toni, Luca; Fanelli, Flaminia; Mezzullo, Marco; Pelusi, Carla; Pagotto, Uberto; Belli, Serena; Granata, Antonio R. M.; Roli, Laura; Rochira, Vincenzo; et al.
Abstract: Background: It has recently been suggested that the hypergonadotropic hypogonadism characterizing Klinefelter syndrome (KS) might not be due to a steroidogenic dysfunction per se, but mainly to an altered testosterone (T) secretion into the bloodstream. However, the Leydig cell functionality remains incompletely studied in KS, and new markers should be considered. Previous data indicated that chronic hCG stimulation influences the production of both insulin‐like peptide 3 (INSL3) and 25‐hydroxy‐vitamin D (25‐VD) in eugonadal men. Aim of the study: To evaluate INSL3 and 25‐VD serum levels, as markers of Leydig cell functionality, in association with sex steroids, after an acute hCG test in a group of KS patients and healthy volunteers. Methods: A retrospective analysis of a prospective case‐control clinical trial was carried out. KS patients (n = 11) and age‐matched healthy controls (n = 11) provided a basal blood sample (V0) immediately followed by a single intramuscular injection of hCG 5000 IU. Blood samples were taken in the following five days (V1‐V5). Results: At baseline, INSL3 was lower in KS patients compared with controls ( P = .007). When adjusted for INSL3 levels, the production of steroids was similar between KS patients and controls. 25‐VD was in the insufficient range both in KS patients and in controls and was not different ( P = .064). Acute hCG stimulation increased neither INSL3 nor 25‐VD in both KS patients and controls. In controls, an inverse correlation was detected between INSL3 levels and body mass index ( P = .020) and waist circumference ( P = .020). Conclusions: INSL3 secretion is independent from steroidogenesis, and its production is mostly not influenced by acute hCG stimulation both in KS men and in controls. INSL3 serum levels should be considered as a marker of Leydig cell differentiation and numbers rather than steroidogenesis. 25‐VD serum levels are also not increased by a single acute hCG administration, which was not able to restore the normal concentrations of 25‐VD.